1997
DOI: 10.2105/ajph.87.4.574
|View full text |Cite
|
Sign up to set email alerts
|

The role of diabetes mellitus in the higher prevalence of tuberculosis among Hispanics.

Abstract: Diabetes mellitus remains a significant risk factor for tuberculosis in the United States. The association is especially notable in middle-aged Hispanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
122
4
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 25 publications
4
122
4
4
Order By: Relevance
“…2,3 Prior to the 1950s reports of an association between diabetes (primarily type 1) and TB were frequent in the literature, but they waned as insulin and drugs against TB became available. 4,5 This association (now with type 2 diabetes) was recognized again in the 1990s [6][7][8][9] and is currently supported by a growing body of literature. [6][7][8][9][10][11][12][13][14][15][16][17] According to a recent meta-analysis, diabetes patients have three times the risk of contracting TB as non-diabetics (95% confidence interval, CI: 2.3-4.3) 18 and studies report the fraction of TB cases attributable to diabetes to be between 15% and 25%.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…2,3 Prior to the 1950s reports of an association between diabetes (primarily type 1) and TB were frequent in the literature, but they waned as insulin and drugs against TB became available. 4,5 This association (now with type 2 diabetes) was recognized again in the 1990s [6][7][8][9] and is currently supported by a growing body of literature. [6][7][8][9][10][11][12][13][14][15][16][17] According to a recent meta-analysis, diabetes patients have three times the risk of contracting TB as non-diabetics (95% confidence interval, CI: 2.3-4.3) 18 and studies report the fraction of TB cases attributable to diabetes to be between 15% and 25%.…”
Section: Introductionmentioning
confidence: 85%
“…[6][7][8][9][10][11][12][13][14][15][16][17] According to a recent meta-analysis, diabetes patients have three times the risk of contracting TB as non-diabetics (95% confidence interval, CI: 2.3-4.3) 18 and studies report the fraction of TB cases attributable to diabetes to be between 15% and 25%. 9,13,16 The biological basis for the association between both diseases is not fully understood but studies suggest that diabetes depresses the immune response, which in turn facilitates infection with Mycobacterium tuberculosis and/or progression to symptomatic disease. This is corroborated by the fact that diabetes is generally diagnosed before TB develops.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 If TB is not perceived to be a serious health risk, whether due to language barriers or other reasons, the likelihood of reducing the prevalence of TB in homeless populations will not be diminished. The prevalence of latent TB is higher among African Americans, Latinos, Asians/Pacific Islanders, and American Indians/Alaskan Natives compared to Whites, [20][21][22] with rates consistently highest among African Americans and Latinos. 8,21,23,24 Prevalence is amplified for minority homeless populations.…”
Section: Introductionmentioning
confidence: 93%
“…10 A case-control study in California involving 5,290 hospital discharges who had a diagnosis of TB found that the risk of TB attributable to DM among middle-aged Hispanics (25.2%) was similar to that attributable to HIV infection (25.5%), whereas among the middle-aged White population the risk of TB attributable to DM (2.4%) was far lower than the risk attributable to HIV (45.7%). 11 …”
Section: Diabetes Increases the Incidence Of Tbmentioning
confidence: 99%